2022
DOI: 10.3892/etm.2022.11225
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin attenuates lipopolysaccharide‑induced inflammation and oxidative stress, and promotes the osteogenic differentiation of human periodontal ligament stem cells through enhancing sirtuin3 expression

Abstract: Periodontitis is a common inflammatory gum disease that destroys the periodontal tissue. Gastrodin (GAS) is the predominant bioactive component of Gastrodia elata Blume and exhibits anti-inflammatory, anti-apoptotic and antioxidant effects in various diseases, including bone-related diseases. The aim of the present study was to investigate whether GAS could protect lipopolysaccharide (LPS)-treated human periodontal ligament stem cells (hPDLSCs) against injury and inflammation, and to determine the potential un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In a recent study, researchers showed that gastrodin reduced inflammation in kidney cells exposed to a hyperglycemic environment. [87] Finally, Feng et al [14] indicated that gastrodin enhanced the expression of sirtuin 3 (SIRT3). The enzyme that is crucial in regulating the inflammatory response and oxidative stress, as well as governing cell differentiation, is called Nuclear factor kappa B (NF-kB).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, researchers showed that gastrodin reduced inflammation in kidney cells exposed to a hyperglycemic environment. [87] Finally, Feng et al [14] indicated that gastrodin enhanced the expression of sirtuin 3 (SIRT3). The enzyme that is crucial in regulating the inflammatory response and oxidative stress, as well as governing cell differentiation, is called Nuclear factor kappa B (NF-kB).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…The enzyme that is crucial in regulating the inflammatory response and oxidative stress, as well as governing cell differentiation, is called Nuclear factor kappa B (NF-kB). [14] It also promoted the osteogenic differentiation of human periodontal ligament stem cells (HPLSC). In conclusion, gastrodin demonstrated potential anti-inflammatory activity by inhibiting the production of proinflammatory cytokines, suppressed immune cell activation, inhibited the expression of COX-2 and iNOS enzymes, and regulated the NF-kB signaling pathway.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…LPS can activate the immune response and induce the expression of pro‐inflammatory cytokines such as tumor necrosis factor α (TNF‐α), interleukin (IL)‐1β, and interleukin (IL)‐6, resulting in periodontal inflammation and bone resorption (Ding et al, 2017). Under inflammation conditions, hPDLSCs suffer long‐term hypoxia and ischemic conditions, which greatly attenuates their abilities to self‐renew and perform osteogenesis (An et al, 2016; Feng, 2022). Many transcription factors and cellular signaling pathways are involved in the expression of pro‐inflammatory mediators (Diomede et al, 2017; Park et al, 2012; Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%